DETERMINAN PENDAPATAN KEDAI KOPI DI KECAMATAN TABANAN - Dharmasena, Gede Bayu Kresna; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 14 No 1 (2025): Vol.14.No.1. JANUARI 2025 [1-122]DO - 10.24843/EEP.2025.v14.i01.p01, 2025)
Micro, small and medium enterprises (MSMEs) in economic development can reduce inequality in the uneven development process. This research aims to analyze the simultaneous and partial influence of capital variables, entrepreneurial attitudes, and working hours on income, and analyze the role of purchasing power in moderating the influence of capital on coffee shop income in Tabanan District. The number of samples was taken using the saturated sampling method. The data analysis technique used is moderated regression analysis. The results of the research concluded that simultaneously capital, working hours, entrepreneurial behavior and purchasing power have a significant influence on the income of coffee shops in Tabanan District. Partially, capital, working hours, entrepreneurial behavior and purchasing power each have a significant positive influence on the income of coffee shops in Tabanan District. Purchasing power is able to moderate the influence of capital on coffee shop income in Tabanan District to become stronger. This means that purchasing power is able to strengthen the influence of capital on coffee shop income in Tabanan District. Key words: capital, working hours, entrepreneurial behavior, income, purchasing power